Investigating the relationship between social media consumption and fear of crime: A partial analysis of mostly young adults. (December 2017) - Intravia, Jonathan; Wolff, Kevin T.; Paez, Rocio; Gibbs, Benjamin R.
Abstract: Theories of media effects have long established a link between media consumption and fear of crime. To date, prior investigations have almost exclusively focused on traditional types of media content (e.g., television news) or entertainment media (e.g., crime-related shows). However, less is known how social media consumption may influence individuals' levels of fear. Using data collected from a multisite sample of mostly young adults, the present study assesses: (1) the relationship between various types of social media consumption (overall, general news, and crime-related content) and fear of crime and (2) whether these relationships differ based on key audience characteristics. Findings reveal that overall social media consumption is significantly related to fear of crime and this relationship varies by perceptions of safety. Highlights: The relationship between social media consumption and fear of crime is examined. Greater social media consumption is related to fear among adults. This relationship varies by perceived safety.